2018
DOI: 10.1016/j.jsbmb.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D on gut microbiota in cystic fibrosis

Abstract: This review explores the potential for vitamin D to favorably alter the gut microbiota, given emerging evidence of the role of vitamin D in controlling mucosal inflammation in the gut. It will focus on cystic fibrosis (CF) patients, a population with both vitamin D deficiency due to gut malabsorption and an altered gut microbiota composition. Recent evidence shows that vitamin D acts to maintain the integrity of the gut mucosal barrier by enhancement of intercellular junctions that control mucosal permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 58 publications
0
35
0
4
Order By: Relevance
“…Alternatively, low 25OHD levels are related to up-regulation of proinflammatory cytokines and an impaired epithelial barrier, leading to enhanced inflammation and dysbiosis. 3 Furthermore, we have previously shown that lower circulating 25OHD levels associate with specific nasopharyngeal metabolomic signature – e.g., enriched proinflammatory lipids that can serve as mediators in the microbiome-host interactions in the airways. 2 …”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, low 25OHD levels are related to up-regulation of proinflammatory cytokines and an impaired epithelial barrier, leading to enhanced inflammation and dysbiosis. 3 Furthermore, we have previously shown that lower circulating 25OHD levels associate with specific nasopharyngeal metabolomic signature – e.g., enriched proinflammatory lipids that can serve as mediators in the microbiome-host interactions in the airways. 2 …”
Section: To the Editormentioning
confidence: 99%
“…2 Vitamin D compounds have pleiotropic regulatory roles on both innate and adaptive immune responses. 3 Low levels of 25-hydroxyvitamin D (25OHD), the major circulating form of vitamin D, have been found to be associated with higher risk and severity of acute respiratory infections (ARIs) in children. 4 Recent studies also have reported an association of maternal 5 and cord blood 6 vitamin D levels with infant gut microbiota.…”
Section: To the Editormentioning
confidence: 99%
“…Due to gut malabsorption, in cystic fibrosis patients, vitamin D deficiency frequently occurs (Sexauer et al, 2015). Given the vital role of vitamin D in mediating gut mucosal inflammation, vitamin D as a therapeutic approach for gut microbiota modification in cystic fibrosis has been attempted (Vanstone et al, 2015;Kanhere et al, 2018). Vitamin D can develop a healthy gut microbiota, maintain the integrity of the gut mucosal barrier, and allow beneficial bacteria to outcompete opportunistic pathogens (Kanhere et al, 2018).…”
Section: Supplementing Micronutrients To Regulate Gut Microbiotamentioning
confidence: 99%
“…Given the vital role of vitamin D in mediating gut mucosal inflammation, vitamin D as a therapeutic approach for gut microbiota modification in cystic fibrosis has been attempted (Vanstone et al, 2015;Kanhere et al, 2018). Vitamin D can develop a healthy gut microbiota, maintain the integrity of the gut mucosal barrier, and allow beneficial bacteria to outcompete opportunistic pathogens (Kanhere et al, 2018). Enhancing intercellular junctions, reducing proinflammatory cytokines such as IL-8, and inhibiting apoptosis of intestinal epithelial cells might be involved in the action mechanism of vitamin D (Kanhere et al, 2018).…”
Section: Supplementing Micronutrients To Regulate Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation